2021
DOI: 10.3390/jcm10204747
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Level of Post Traumatic Growth in Kidney Transplant Recipients via Network Analysis

Abstract: Although kidney transplant can lead to psychiatric disorders, psychosocial syndromes and demoralization, a positive post-traumatic growth (PTG) can occur in kidney transplant recipients (KTRs). However, the PTG-Inventory (PTGI), a reliable tool to measure PTG is scarcely used to explore the effect of this stressful event in KTRs. Thus, the purpose of our study was to assess the level of PTG and its correlation with demoralization, physical and emotional symptoms or problems via network analysis in KTRs. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Liver transplant recipients who have living donor liver transplantation generally feel deep gratitude toward the organ donor, and the intimacy with the donor ties recipients more tightly to living by convincing them that they are really loved by the people around them, and also, this intimacy will reinforce recipients’ social support perceptions ( 26 , 27 ). In previous studies, it was identified that kidney patients who had living donor kidney transplantation had higher levels of post-traumatic growth than those who had cadaveric donor kidney transplantation ( 28 , 29 ). In our study, liver transplant recipients with living donor had higher post-traumatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplant recipients who have living donor liver transplantation generally feel deep gratitude toward the organ donor, and the intimacy with the donor ties recipients more tightly to living by convincing them that they are really loved by the people around them, and also, this intimacy will reinforce recipients’ social support perceptions ( 26 , 27 ). In previous studies, it was identified that kidney patients who had living donor kidney transplantation had higher levels of post-traumatic growth than those who had cadaveric donor kidney transplantation ( 28 , 29 ). In our study, liver transplant recipients with living donor had higher post-traumatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have employed the network analysis approach to investigate the cross‐sectional relationships between items of PTG (Adamkovič et al, 2022; Baník et al, 2022; Battaglia et al, 2021; Bellet et al, 2018; Ma et al, 2022; Peters et al, 2021; Steinberg et al, 2022; Wang et al, 2022). For instance, significant positive correlations have been found between “priority change” and “appreciation of life,” “new interest” and “new path” (Baník et al, 2022), “closeness” and “valuing others” (Peters et al, 2021), “spirituality” and “faith” (Baník et al, 2022; Peters et al, 2021), and “handle difficulties” and “do better things” (Ma et al, 2022; Peters et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to progress in desensitization and preoperative monitoring of donor-specific antibodies, this Special Issue also provided insights into the monitoring and management of chronic active antibody-mediated rejection [17]. Furthermore, investigators also shed light on post-transplant complication research, including osteoporotic fractures [9], diarrhea [15], psychological changes [19], and recurrent primary disease [17].…”
mentioning
confidence: 96%
“…In this Special Issue, "Progress and Recent Advances in Solid Organ Transplantation", researchers from different disciplines with different expertise and resources highlighted the novelty of their recent investigations in the field of organ transplantation, including issues related to donors, allografts, and patient survival [8][9][10][11][12][13][14][15][16][17][18][19][20]. While there have been significant advances in regional and national kidney paired-donation programs in matching incompatible pairs, data suggest that there may be a role for desensitization in select cases to facilitate organ transplantation [21].…”
mentioning
confidence: 99%